A field simulation study of the effectiveness of penalty kick strategies in soccer: Late alterations of kick direction increase errors and reduce accuracy - van der Kamp, J. (Journal of Sports Sciences, 2006)
This field experiment investigated the relative merits of approaching the penalty kick with either a keeper-independent or keeper-dependent strategy. In the keeper-independent strategy, the shooter selects a target location in advance and disregards the goalkeeper's actions during the run-up. In the keeper-dependent strategy, the shooter makes a decision resting on the anticipation of the goalkeeper's movements during the run-up. Ten intermediate-level soccer players shot at one of two visually specified targets to the right and left side of the goal. In the keeper-independent strategy condition, participants were told that the visually specified target would not change. In the keeper-dependent strategy condition, participants were told that in half of the trials the visually specified target would change side at different times before ball contact, indicating that the direction of the kick needed to be altered. The results showed that penalty-taking performance was apt to be less than perfect in the keeper-dependent strategy condition. A decrease in the time available to alter kick direction resulted in a higher risk of not only an incorrect but also inaccurate shot placement. It is concluded that anticipating the goalkeeper's movements may degrade penalty kick performance, mainly due to insufficient time to modify the kicking action.